1983
DOI: 10.1113/jphysiol.1983.sp014846
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular analysis of geniculo‐cortical connectivity in area 17 of the cat.

Abstract: SUMMARY1. The latencies ofexcitatory and inhibitory post-synaptic potentials (e.p.s.p.s and i.p.s.p.s) evoked by electrical stimulation of afferents from the lateral geniculate nucleus were recorded in neurones ofarea 17 of the cat visual cortex. After application of an extrapolation procedure to compensate for the conduction time of the afferent axons, a histogram oflatencies formed three distinct peaks. Potentials in each ofthese were interpreted as being mediated by mono-, di-and trisynaptic pathways.2. Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
202
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(222 citation statements)
references
References 51 publications
19
202
1
Order By: Relevance
“…Synaptic potentials arising from these two distinct pathways differ in latency (Ferster and Lindström, 1983), with disynaptic inputs arriving at least 1 ms later than monosynaptic inputs (and trisynaptic inputs arriving at least 2 ms later). Many cortical cells receive both monosynaptic and polysynaptic excitatory inputs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic potentials arising from these two distinct pathways differ in latency (Ferster and Lindström, 1983), with disynaptic inputs arriving at least 1 ms later than monosynaptic inputs (and trisynaptic inputs arriving at least 2 ms later). Many cortical cells receive both monosynaptic and polysynaptic excitatory inputs.…”
Section: Resultsmentioning
confidence: 99%
“…3B). The division between putative monosynaptic and polysynaptic cells was chosen based on the shape of the distribution of measured latencies, as well as on previous studies using similar methods (Ferster and Lindström, 1983;Chung and Ferster, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, this is also the main direction of flow of excitation mediated by spiny stellate and star pyramidal cells' axons (Lund et al, 1979;Ferster and Lindstrom, 1983;Armstrong-James et al, 1992;Anderson et al, 1994;Lubke et al, 2000). Thus, inhibition in the cortex is inextricably linked to excitation, apparently following it along its intracortical course.…”
Section: Excitatory and Inhibitory Flow After A Thalamocortical Volleymentioning
confidence: 99%
“…Because putative inhibitory barrel neurons often have multiwhisker receptive fields (Simons and Carvell, 1989;Swadlow, 1989;Welker et al, 1993), type A neurons may also mediate the adjacent-whisker inhibition observed in vivo (Simons, 1995;Goldreich et al, 1999). Types B, D, and E neurons, with a sphere of influence extending to layers II/III, probably mediate the strong disynaptic inhibition observed in supragranular neurons in vivo (Ferster and Lindstrom, 1983;Kyriazi et al, 1998;Brumberg et al, 1999;Zhu and Connors, 1999) or in vitro (Agmon and Connors, 1992). Finally, inhibitory neurons of morphological type E, with axonal trees that extend tangentially at least one barrel width on either or both sides of the column of origin, will generate the short-latency cross-column inhibition that is a prominent feature in supragranular layers of mouse barrel cortex in vivo (Welker et al, 1993).…”
Section: Morphological Types Of Inhibitory Interneurons and Their Funmentioning
confidence: 99%
See 1 more Smart Citation